Combined energetic, economic and climate change assessment of heat pumps for industrial waste heat recovery. (1st May 2022) - Jovet, Yoann; Lefèvre, Frédéric; Laurent, Alexis; Clausse, Marc
Highlights: Climate change footprint is studied taking the life cycle of the whole energy system. Mechanical heat pumps (MHP) are considered as alternatives to natural gas boilers. MHP can help to achieve the Paris Agreement targets in EU countries by 2050. Energy price ratios to make MHP competitive are identified for different performance. Impact of carbon tax on MHP competitiveness is assessed for several EU members. Abstract: The recovery of waste heat represents a promising opportunity to reduce greenhouse gas (GHG) emissions from industrial sectors. The current development of heat recovery technologies can provide industries with several options for retrofitting their heat generation systems. Although past studies estimated the resulting savings in GHG emissions for specific industries or facilities, work is still needed to fully substantiate the expected benefit and the competitiveness of these alternatives, taking into account data at country scale (e.g. long-term reduction targets, energy cost, etc.). Hence, in this study, a new methodology is developed to determine the minimum conditions for waste heat recovery solutions to enable compliance with the targets from the Paris Agreement, taking 2030 and 2050 as reference years. It is applied to several industrial sectors for 24 EU countries, focusing on mechanical heat pump solutions (MHPs). Results indicate that all countries are compliant in 2050 for MHP integration with low temperature lift (like ammonia production) and 21 countries are compliant for high temperature lift (like food industry). The main constraint to the development of the MHP technology in 2030 is found to be economic, while in 2050, the main barrier for countries that do not reach the reduction targets is a too high carbon intensity of electricity generation. To accommodate the relatively long lifetime of the heat production system, the future MHP roadmap should therefore anticipate these potential barriers including carbon footprint of electricity network, working fluids and gas to electricity price ratio. In addition to meeting the 2030 requirements by a large margin, this strategy would factor in constraints associated with the long-term investments in MHPs. To further expand such foresight analysis, our methodology can be duplicated to other technologies than MHPs, so it can help industry decision-makers select the most suitable waste heat recovery options for a given industrial process in a specific country.